Preparation method and application of surface glue starch with three-dimensional interpenetrating interlayer structure

By using a new type of surface glue starch made of clay/starch-based material with a three-dimensional interspersed layer structure, the problem of low surface strength of grass fiber and waste paper recycling paper is solved, and the mechanical properties of corrugated cardboard are significantly improved and environmentally friendly. Continuous production mode.

CN119432950APending Publication Date: 2025-02-14TIANJIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411380747.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the existing papermaking technology, the paper made from grass fibers and waste paper after recycling has low surface strength and poor stability, and the use of traditional chemicals and synthetic materials has been questioned about environmental protection, resulting in high production costs.

Method used

A clay/starch-based material with a three-dimensional interspersed layer structure is used to form a new type of surface glue starch through specific ratios and process treatments, which is used to improve the mechanical properties of corrugated cardboard.

Benefits of technology

It significantly improves the folding resistance, breakage and tension resistance index of corrugated cardboard, improves the mechanical properties and printing effect of paper, and reduces production costs, and meets the requirements of environmental protection and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432950A_ABST
    Figure CN119432950A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of surface glue starch with a three-dimensional interpenetrating interlayer structure, and the preparation method is characterized by comprising the following steps: step 1, weighing sodium bentonite, calcium bentonite and kaolin, putting into a conical flask, adding distilled water, sealing, carrying out ultrasonic treatment, and naming as Na-BX, Ca-BX and Kao-X; and 2, adding corn starch into the solution obtained in the step 1, preparing a starch slurry, stirring in a constant-temperature water bath kettle, transferring alpha-amylase, adding into the starch slurry, stirring in the constant-temperature water bath kettle, heating while stirring, and preserving heat to obtain the surface sizing starch. According to the method, no chemical product is added in the preparation process, the safety is guaranteed, meanwhile, the environment-friendly concept of greenness, low carbon and sustainability is considered, and the sizing performance of the prepared surface sizing starch is better than that of original starch.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of pulping and papermaking, and in particular to a preparation method and application of surface glue starch with a three-dimensional interpenetrating layer structure. Background Art

[0002] In addition to vigorously developing fast-growing artificial papermaking forests, the rational use of grass fibers and the recycling of waste paper are currently more important ways. More than 90% of my country's papermaking raw materials are straw pulp or secondary and multiple fibers, which results in low surface strength and poor stability of paper after papermaking, and the mechanical strength of paper is prone to decrease after being stored for a period of time. For a long time in the future, the use of grass fibers and the recycling of waste will still be an important source of raw materials in China's papermaking industry. Therefore, improving the performance of surface sizing agents and making paper adapt to the requirements of mechanical properties and printing quality has become an issue that cannot be ignored in the industry.

[0003] At present, the main method to improve the mechanical strength of paper is through the method of internal sizing or surface sizing, among which surface sizing is more common in actual production as a more convenient method. With the improvement of global environmental awareness and the increasingly stringent environmental protection regulations, the chemicals and synthetic materials used in the traditional papermaking process have been questioned. Clay / starch-based materials are regarded as an environmentally friendly alternative due to their natural and degradable properties, and have attracted the attention of the papermaking industry. Compared with traditional chemicals and synthetic materials, they are low in cost and easy to obtain, which can reduce the cost of papermaking production. In the current competitive market environment, reducing production costs is one of the goals pursued by papermaking companies. Bentonite, kaolin and starch are natural resources with abundant reserves and renewability, which can achieve sustainable utilization of resources. The papermaking industry has been seeking more environmentally friendly and sustainable production methods, and the research and application of clay / starch-based materials are in line with this development trend. Clay / starch-based materials have excellent ink absorption and water resistance, which can improve the smoothness, mechanical strength, glossiness and printing effect of paper, and improve the strength and printing performance of paper. With the continuous advancement of science and technology, the research and application of new materials continue to emerge. The research on clay / starch-based materials in the papermaking field is also driven by technological innovation, which brings new development opportunities to the papermaking industry by continuously improving material properties and production processes.

[0004] In view of this, the present invention proposes a method for preparing a novel surface starch with a three-dimensional interpenetrating layer structure. The formation of this interpenetrating layer structure is mainly related to the ratio of bentonite, kaolin and starch. Under a certain ratio, this interpenetrating layer structure can be formed, and this process can regulate the long- and short-range order inside the starch particles, thereby improving the mechanical strength of the corrugated board. Summary of the invention

[0005] In view of this, the present invention provides a preparation method and application of surface glue starch with a three-dimensional interpenetrating layer structure.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] The method for preparing a surface starch having a three-dimensional interpenetrating layer structure comprises the following steps:

[0008] Step 1: Weigh sodium bentonite, calcium bentonite and kaolin in a conical flask, add distilled water, seal, ultrasonicate, and name them Na-BX, Ca-BX, Kao-X;

[0009] Step 2: Take the solution obtained in step 1 and add corn starch to prepare starch slurry, place it in a constant temperature water bath and stir, transfer α-amylase to the starch slurry, keep stirring in the constant temperature water bath, and after completion, heat up while stirring and keep warm to obtain surface sizing starch.

[0010] Preferably, in step 1, the addition amount of sodium bentonite, calcium bentonite and kaolin is 0.5% to 5% of the mass of 10g of absolute dry corn starch, and the optimal ratio is 1.5%, 2.0% and 5.0% respectively.

[0011] Preferably, in step 1, the amount of distilled water added is 88.47 g.

[0012] Preferably, in step 1, the ultrasonic time is 10 to 30 minutes, wherein the optimal time is 30 minutes.

[0013] Preferably, in step 2, the amount of corn starch added is 11.53 g.

[0014] Preferably, in step 2, the mass concentration of the starch slurry is 10-20%.

[0015] Preferably, in step 2, the temperature of the constant temperature water bath is 35-40° C., the stirring time is 5-10 min, and the stirring speed is 300 rpm.

[0016] Preferably, in step 2, the dosage of α-amylase is 2.0-18.5u / g, and the enzyme activity is 45623u / ml; wherein, the optimal dosage of α-amylase is 6.8u / g.

[0017] Preferably, in step 2, the temperature is raised to 85-90°C, the heating rate is 1°C / min, and the insulation time is 20-40min; wherein, the optimal initial temperature is 38°C, the stirring time is 10min, the optimal termination insulation temperature is 85°C, the optimal insulation time is 30min, and the optimal insulation temperature is 80°C.

[0018] The invention discloses a method for preparing surface starch with three-dimensional interpenetrating layer structure and its application in improving the mechanical properties of corrugated board.

[0019] Compared with the prior art, the present invention has achieved the following technical effects:

[0020] (1) The present invention is based on the construction of clay / starch-based biomaterials, and through the synergistic effect of α-amylase, surface-sizing starch is obtained under a continuous cooking process. The preparation method is highly operable, and no environmentally harmful components are added during the preparation process, which is green and environmentally friendly. In addition, the preparation process is simple, the reaction conditions are mild and controllable, and it is suitable for large-scale manufacturing, and has broad application prospects in the field of papermaking technology;

[0021] (2) The raw materials used in the present invention are natural resources such as bentonite, kaolin and starch, which have abundant reserves and sustainability, and can achieve sustainable utilization of resources, which is more in line with the more environmentally friendly and sustainable production method that the papermaking industry has been looking for;

[0022] (3) The novel starch latex constructed by the present invention reduces the long-range order of starch particles and increases the short-range order;

[0023] (4) Compared with corn starch, the new latex of the present invention has a significantly lower degree of crystallinity, and the long chains in the starch granules are sheared into short chains, which is beneficial to improving the reinforcing efficiency of the surface sizing starch. As a result, the folding endurance, bursting index and tensile index of the corrugated board are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 (a) is a scanning electron microscope image of a sodium bentonite / starch-based material having a three-dimensional interpenetrating layer structure, a method for preparing a surface starch having a three-dimensional interpenetrating layer structure, and an application thereof;

[0025] Figure 1 (b) is a scanning electron microscope image of a calcium-based bentonite / starch-based material having a three-dimensional interpenetrating layer structure, a method for preparing a surface starch having a three-dimensional interpenetrating layer structure and an application thereof;

[0026] Figure 1 (c) is a scanning electron microscope image of a kaolin / starch-based material for the preparation method and application of the surface glue starch having a three-dimensional interpenetrating layer structure of the present invention;

[0027] Figure 2 (a) is an X-ray diffraction data diagram of sodium bentonite / starch-based materials of the present invention for preparing a starch with a three-dimensional interpenetrating layer structure and its application;

[0028] Figure 2 (b) is an X-ray diffraction data diagram of a calcium-based bentonite / starch-based material of the present invention for preparing a surface starch having a three-dimensional interpenetrating layer structure and its application;

[0029] Figure 2 (c) is an X-ray diffraction data diagram of kaolin / starch-based materials for the preparation method and application of the surface starch with three-dimensional interpenetrating layer structure of the present invention;

[0030] Figure 3 (a) is a Fourier infrared spectrum of a sodium bentonite / starch-based material having a three-dimensional interpenetrating layer structure and a method for preparing the surface starch and its application in the present invention;

[0031] Figure 3 (b) is a Fourier infrared spectrum of the calcium-based bentonite / starch-based material of the present invention for preparing the surface starch with three-dimensional interpenetrating layer structure and its application;

[0032] Figure 3 (c) is a Fourier infrared spectrum of kaolin / starch-based materials for the preparation method and application of the surface starch with three-dimensional interpenetrating layer structure of the present invention;

[0033] Figure 4 The invention discloses a method for preparing a surface starch having a three-dimensional interpenetrating layer structure and the influence of the applied sodium bentonite / starch-based material on the mechanical properties of corrugated paperboard;

[0034] Figure 5 The invention discloses a method for preparing a surface starch having a three-dimensional interpenetrating layer structure and the influence of the applied calcium-based bentonite / starch-based material on the mechanical properties of corrugated paperboard;

[0035] Figure 6 The invention discloses a method for preparing a surface starch with a three-dimensional interpenetrating layer structure and the influence of applied kaolin / starch-based materials on the mechanical properties of corrugated paperboard. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The present invention discloses a method for preparing a surface glue starch having a three-dimensional interpenetrating layer structure, comprising the following steps:

[0038] Step 1: weigh 0.5% to 5% of sodium bentonite, calcium bentonite and kaolin relative to 10g of absolute dry corn starch in a conical flask, add 88.47g of distilled water, seal, place in an ultrasonic cleaning device for 10 to 30 minutes, and name them as Na-BX, Ca-BX, Kao-X, such as Na-B0.5% means a solution with a ratio of 0.5%;

[0039] Step 2: Take the solution obtained in step 1 and add 11.53g corn starch to prepare a starch slurry with a mass concentration of 10-20%, place it in a constant temperature water bath at 35-40°C and stir it at 300rpm for 5-10min, take 2.0-18.5u / g of α-amylase with an enzyme activity of 45623u / ml and add it to the starch slurry, keep it in a constant temperature water bath at 35-40°C and stir it for 5-10min, and then heat it to 85-90°C while stirring, the heating rate is 1°C / min, and the temperature is kept for 20-40min to obtain surface sizing starch.

[0040] The invention discloses a method for preparing surface starch with three-dimensional interpenetrating layer structure and its application in improving the mechanical properties of corrugated board.

[0041] The best cooking process for surface sizing starch is:

[0042] Prepare a starch slurry with a mass fraction of 10% with deionized water, then place it in a 38°C water bath and stir for 5 minutes, add 6.8u / g of α-amylase to the slurry and stir for 10 minutes to mix it evenly, then continue to heat up to a termination temperature of 85°C, and keep it at 85°C for 30 minutes, naturally cool the slurry temperature to 80°C, add deionized water with a temperature of 80°C to ensure that the concentration of the surface sizing starch slurry reaches 10%, and place the diluted surface sizing starch slurry in a water bath with a temperature of 80°C for constant temperature storage for later use.

[0043] Embodiment 1:

[0044] A method for preparing a novel surface gelatin starch having a three-dimensional interpenetrating layer structure comprises the following steps:

[0045] Step 1: Weigh 0.5% sodium bentonite relative to 10g of absolute dry corn starch (solid content 86.71%), add 88.47g of distilled water to obtain a corresponding solution, ultrasonicate in an ultrasonic cleaner for 30min, take out, add 11.53g of corn starch, stir evenly, and obtain a sodium bentonite / starch-based material with a ratio of 0.5%, i.e., Na-B0.5%, which is retained for later use;

[0046] Step 2: Stir the solution of step 1 in a constant temperature water bath at 38°C for 5 minutes to make it evenly mixed, then add 6.8U / g of α-amylase to the starch slurry and stir it for 10 minutes at 38°C at a speed of 300rpm, keep stirring and continue to heat to 85°C, and keep it warm for 30 minutes to obtain surface sizing starch;

[0047] Gluing the surface of corrugated cardboard: take the surface glue starch in step 2 and add a certain amount of 85°C deionized water to restore the surface glue starch liquid to a solid content of 10%, and use a semi-automatic coating machine to glue the surface of the corrugated cardboard. The surface glue amount is 3g / m2. After gluing, place it in a 105°C forced air oven to dry for 5 minutes, then calender the paper, and finally place the paper sample in a constant temperature and humidity laboratory at 23±1°C and 50±2%RH for 24 hours to balance, and then measure the physical properties of the paper.

[0048] The measurement results show that the surface sizing starch prepared with Na-B0.5% sample has a folding endurance of 14.6±3 times, a bursting index of 1.9±0.5Kpa·m2 / g, a transverse tensile index of 17.3±1.0N·m / g, and a longitudinal tensile index of 43.5±1.0N·m / g after sizing corrugated board. Compared with the surface sizing starch prepared with native starch Nst in the comparative example, the longitudinal tensile index, folding endurance, bursting index and transverse tensile index are slightly increased, but the overall difference is not large.

[0049] Embodiment 2:

[0050] A method for preparing a novel surface gelatin starch having a three-dimensional interpenetrating layer structure comprises the following steps:

[0051] Step 1: Except for weighing 10 g of 1.0% sodium bentonite relative to absolute dry corn starch (solid content 86.71%), the rest is the same as described in Example 1 to obtain a Na-B 1.0% sample to be retained for later use;

[0052] Step 2: Same as step 2 of Example 1;

[0053] Step 3: Same as step 3 in Example 1.

[0054] The measurement results show that the surface sizing starch prepared with Na-B1.0% sample has a folding endurance of 15±3 times, a bursting index of 1.9±0.5Kpa·m2 / g, a transverse tensile index of 18.5±1.0N·m / g, and a longitudinal tensile index of 47.6±1.0N·m / g after sizing corrugated board. Compared with the surface sizing starch prepared with native starch Nst in the comparative example, the longitudinal tensile index is increased by about 9.9%, and the folding endurance, bursting index and transverse tensile index are all increased by about 10%.

[0055] Embodiment 3:

[0056] A method for preparing a novel surface gelatin starch having a three-dimensional interpenetrating layer structure comprises the following steps:

[0057] Step 1: Except for weighing 10 g of sodium bentonite at 1.5% by weight relative to the absolute dry corn starch (solid content 86.71%), the rest is the same as described in Example 1 to obtain a Na-B 1.5% sample to be retained for later use;

[0058] Step 2: Same as step 2 of Example 1;

[0059] Step 3: Same as step 3 in Example 1.

[0060] The test results show that the surface sizing starch prepared by using Na-B1.5% sample has a folding endurance of 16.4±3 times, a bursting index of 2.0±0.5Kpa·m2 / g, a transverse tensile index of 19.5±1.0N·m / g, and a longitudinal tensile index of 50.8±1.0N·m / g after sizing the corrugated board. Compared with the surface sizing starch prepared by the comparative example native starch Nst, the folding endurance is increased by about 13.9%, the longitudinal tensile index is increased by about 17.3%, the bursting index is increased by about 5.3%, and the transverse tensile index is increased by about 14.7%. In addition, it can be seen from the SEM image that the three-dimensional interlaced layer structure is well formed at this time, with a good structural style, such as Figure 1 (a) shown.

[0061] Embodiment 4:

[0062] A method for preparing a novel surface gelatin starch having a three-dimensional interpenetrating layer structure comprises the following steps:

[0063] Step 1: Except for weighing 10 g of 2.0% sodium bentonite relative to the absolute dry corn starch (solid content 86.71%), the rest is the same as described in Example 1 to obtain a Na-B 2.0% sample to be retained for later use;

[0064] Step 2: Same as step 2 of Example 1;

[0065] Step 3: Same as step 3 in Example 1.

[0066] The test results show that the surface sizing starch prepared with Na-B2.0% sample has a folding endurance of 14.6±3 times, a bursting index of 1.9±0.5Kpa·m2 / g, a transverse tensile index of 18.5±1.0N·m / g, and a longitudinal tensile index of 47.3±1.0N·m / g after sizing the corrugated board. Compared with the surface sizing starch prepared with the reference starch Nst, the longitudinal tensile index is increased by about 9.2%, and the folding endurance, bursting index, and transverse tensile index are slightly increased, but the overall difference is not large. In addition, from Figure 1 (a) It can be seen that the three-dimensional interpenetrating layer structure is not well formed at this time.

[0067] Embodiment 5:

[0068] A method for preparing a novel surface gelatin starch having a three-dimensional interpenetrating layer structure comprises the following steps:

[0069] Step 1: Except for weighing 10g of sodium bentonite at 2.5% by weight relative to the absolute dry corn starch (solid content 86.71%), the rest is the same as described in Example 1 to obtain a Na-B 2.5% sample to be retained for later use;

[0070] Step 2: Same as step 2 of Example 1;

[0071] Step 3: Same as step 3 in Example 1.

[0072] The measurement results show that the surface sizing starch prepared with Na-B2.5% sample has a folding endurance of 12.6±3 times, a bursting index of 1.9±0.5Kpa·m2 / g, a transverse tensile index of 16.2±1.0N·m / g, and a longitudinal tensile index of 38.3±1.0N·m / g after sizing corrugated board. Compared with the surface sizing starch prepared with the comparative example native starch Nst, the longitudinal tensile index, folding endurance, bursting index and transverse tensile index all show a downward trend.

[0073] Embodiment 6:

[0074] A method for preparing a novel surface gelatin starch having a three-dimensional interpenetrating layer structure comprises the following steps:

[0075] Step 1: Except for weighing 10g of 5.0% sodium bentonite relative to the absolute dry corn starch (solid content 86.71%), the rest is the same as described in Example 1 to obtain a Na-B 5.0% sample to be retained for later use;

[0076] Step 2: Same as step 2 of Example 1;

[0077] Step 3: Same as step 3 in Example 1.

[0078] The measurement results show that the surface sizing starch prepared with Na-B5.0% sample has a folding endurance of 11.8±3 times, a bursting index of 1.8±0.5Kpa·m2 / g, a transverse tensile index of 15.1±1.0N·m / g, and a longitudinal tensile index of 32.5±1.0N·m / g after sizing corrugated board. Compared with the surface sizing starch prepared with the comparative example native starch Nst, the folding endurance, longitudinal tensile index, bursting index and transverse tensile index are greatly reduced.

[0079] Comparative Example 1:

[0080] A method for preparing a novel surface gelatin starch having a three-dimensional interpenetrating layer structure comprises the following steps:

[0081] Step 1: except that the raw material is calcium-based bentonite, the rest is the same as step 1 of Example 1;

[0082] Step 2: Same as step 2 of Example 1;

[0083] Step 3: Same as step 3 in Example 1.

[0084] Comparative Example 2:

[0085] A method for preparing a novel surface gelatin starch having a three-dimensional interpenetrating layer structure comprises the following steps:

[0086] Step 1: except that the raw material is kaolin, the rest is the same as step 1 of Example 1;

[0087] Step 2: Same as step 2 of Example 1;

[0088] Step 3: Same as step 3 in Example 1.

[0089] Characterization performance test:

[0090] Mechanical properties test: The bursting resistance test refers to GB / T6545-1998 "Determination of the bursting strength of corrugated board", the folding resistance test refers to GB / T457-2008 "Determination of the folding resistance of paper and paperboard", and the tensile strength test refers to GB / T12914-2018 "Determination of the tensile strength of paper and paperboard".

[0091] The SEM image of the three-dimensional interlaced layer structure of the present invention is shown in Figure 1 In, by Figure 1 (a) It can be seen that when the ratio of starch to sodium bentonite is 1.5%, the interlaced layer structure is well formed. If the ratio is too large or too small, this three-dimensional interlaced layer structure cannot be well formed. When the sample is applied as a surface starch on the surface of corrugated cardboard, the mechanical properties of the paper are most significantly improved. Figure 4 As shown, the folding resistance is increased by about 13.9%, the bursting index is increased by about 8.3%, and the transverse and longitudinal tensile indices can be increased by about 14.9% and 17.5% respectively. Figure 1 (b) It can be seen that when the ratio of starch to calcium-based bentonite is 2.0%, the interlaced layer structure is well formed. When the sample is applied to the surface of paper as a surface starch, the mechanical properties of the paper are most significantly improved. Figure 5 As shown, the maximum folding resistance is increased by about 16.7%, the maximum tearing resistance index is increased by about 16.3%, and the transverse and longitudinal tensile indices can be increased by about 13.9% and 10.4% respectively. Figure 1(c) It can be seen that when the ratio of starch to kaolin is 5.0%, this three-dimensional interlaced layer structure is well formed. At this time, when the sample is used as surface starch, the improvement of the mechanical properties of paper is most significant, such as Figure 6 As shown, the folding endurance can be increased by about 11.1% at most, the bursting index can be increased by about 9.3% at most, and the transverse and longitudinal tensile indices can be increased by about 9.9% and 15.7% at most, respectively.

[0092] Figure 4 , 5 The mechanical properties data of Figure 6 show that the degree of enhancement of the mechanical properties of paper by this surface starch is closely related to the three-dimensional interlaced layer structure. When the interlaced layer structure is well formed, the enhancement effect on the mechanical properties is also the most significant. When the ratio is gradually increased to the optimal ratio, the mechanical properties are gradually improved. When the ratio is above the optimal ratio, the mechanical properties will gradually decrease. This shows that the mutual combination of starch particles and bentonite and kaolin has a certain degree. When the saturation state is reached, the continued addition of this inorganic filler will affect the original film structure, thereby affecting its mechanical properties. Figure 2 , 3 The X-ray diffraction data and Fourier infrared spectrum data show that with the addition of fillers, the long-range order of starch particles decreases the most at the optimal ratio, and the degree of destruction of the crystallization zone is also the greatest. Due to the exchange of interlayer cations between starch particles and inorganic fillers, the corresponding crystallization peak of starch particles disappears. The short-range order increases the most at the optimal ratio, and the others are less than this value. The enhancement of short-range order allows the retention of glucans with larger molecular weight in the system. Because glucans with high molecular weight have a good reinforcing effect on the surface of paper fibers, they significantly improve the mechanical properties of corrugated board.

[0093] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a surface starch having a three-dimensional interpenetrating layer structure, characterized in that: The steps include: Step 1: Weigh sodium bentonite, calcium bentonite and kaolin in a conical flask, add distilled water, seal, ultrasonicate, and name them as Na-BX, Ca-BX, and Kao-X; Step 2: Take the solution obtained in step 1 and add corn starch to prepare starch slurry, place it in a constant temperature water bath and stir, transfer α-amylase to the starch slurry, keep stirring in the constant temperature water bath, and after completion, heat up while stirring and keep warm to obtain surface sizing starch.

2. The method for preparing the surface glue starch having a three-dimensional interpenetrating layer structure according to claim 1, characterized in that: In the step 1, the addition amount of sodium bentonite, calcium bentonite and kaolin is 0.5% to 5% of the mass of 10g of absolute dry corn starch, and the optimal ratio is 1.5%, 2.0% and 5.0% respectively.

3. The method for preparing the surface glue starch having a three-dimensional interpenetrating layer structure according to claim 1, characterized in that: In the step 1, the amount of distilled water added is 88.47 g.

4. The method for preparing the surface glue starch having a three-dimensional interpenetrating layer structure according to claim 1, characterized in that: In step 1, the ultrasonic time is 10 to 30 minutes, wherein the optimal time is 30 minutes.

5. The method for preparing the surface glue starch having a three-dimensional interpenetrating layer structure according to claim 1, characterized in that: In the step 2, the amount of corn starch added is 11.53 g.

6. The method for preparing the surface glue starch having a three-dimensional interpenetrating layer structure according to claim 1, characterized in that: In the step 2, the mass concentration of the starch slurry is 10-20%.

7. The method for preparing the surface glue starch having a three-dimensional interpenetrating layer structure according to claim 1, characterized in that: In step 2, the temperature of the constant temperature water bath is 35-40° C., the stirring time is 5-10 min, and the stirring speed is 300 rpm.

8. The method for preparing the surface glue starch having a three-dimensional interpenetrating layer structure according to claim 1, characterized in that: In the step 2, the dosage of α-amylase is 2.0-18.5u / g, and the enzyme activity is 45623u / ml; wherein, the optimal dosage of α-amylase is 6.8u / g.

9. The method for preparing the surface glue starch having a three-dimensional interpenetrating layer structure according to claim 1, characterized in that: In step 2, the temperature is raised to 85-90°C, the heating rate is 1°C / min, and the insulation time is 20-40min; wherein, the optimal initial temperature is 38°C, the stirring time is 10min, the optimal termination insulation temperature is 85°C, the optimal insulation time is 30min, and the optimal insulation temperature is 80°C.

10. Use of the method for preparing the surface glue starch with a three-dimensional interpenetrating layer structure according to any one of claims 1 to 9 in improving the mechanical properties of corrugated paperboard.